Urban ecosystem ecology - Aitkenhead-Peterson, Jacqueline; Volder, Astrid; Crop Science Society of America; Soil Science Society of America (Madison, WI, USA American Society of Agronomy, Inc., 2010)
"This volume deals with the impacts of urbanization on the environment - soils, air and water quality, the animals and humans who live there - and offers some solutions to contemporary problems"--Foreword, page ix.
Urbanization: impacts on clouds, precipitation, and lightning / J.M. Shepherd ... [et al.] -- The urban physical environment: temperature and urban heat islands / Gordon M. Heisler [and] Anthony J. Brazel -- Urban air quality / Sri Juari Santosa -- Birds in urban ecosystems: population dynamics, community structure, biodiversity, and conservation / Eyal Schochat, Susannah Lerman, [and] Esteban Fernandez-Juricic -- Urban mammals / Robert McCleery -- Habitat function in urban riparian zones / Joan G. Ehrenfeld [and] Emilie K. Stander -- Chemical, physical and biological characteristic of urban soils / Richard V. Pouyat ... [at al.] -- Lawn ecology / Thomas W. Cook [and] Erik H. Ervin -- Urban plant ecology / Astrid Volder -- Urban agriculture: a comparative review of allotment and community gardens / David L. Iaquinta [and] Axel W. Drescher -- Urban forestry / Astrid Volder [and] W. Todd Watson -- Inside out: invasive plants and urban environments / Sarah Hayden Reichard -- Urban riparian function / Emilie K. Stander [and] Joan G. Ehrenfeld -- Urban impacts on the water cycle and potential green infrastructure implications / Steven J. Burian [and] Christine A. Pomeroy -- Chemistry of urban, suburban, and rural surface waters / Meredith K. Steele, William H. McDowell, [and] Jacqueline A. Aitkenhead-Peterson -- Urban stream ecology / Allison H. Roy, Michael J. Paul, [and] Seth J. Wenger -- Water use in urban ecosystems: complexity, costs, and services of urban ecohydrology / G. Darrel Jenerette [and] Karrin P. Alstad -- Services in natural and human dominated ecosystems / Jacqueline A. Aitkenhead-Peterson, Meredith K. Steele, [and] Astrid Volder -- Green roofs and garden roofs / D. Bradley Rowe [and] Kristen L. Getter -- Bioretention, low impact development, and stormwater management / Ming-Han Li, Bruce Dvorak, [and] Chan Yong Sung -- Greenspaces, green structure, and green infrastructure planning / Anne R. Beer.
Jointly published with Crop Science Society of America and Soil Science Society of America.
Includes bibliographical references and index.
Keywords: Urban ecology (Biology); Urban ecology (Sociology); City planning